2018
DOI: 10.1186/s13287-018-1093-9
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor regulates phosphate/pyrophosphate regulatory genes in stem cells isolated from human exfoliated deciduous teeth

Abstract: BackgroundBasic fibroblast growth factor (bFGF) regulates maintenance of stemness and modulation of osteo/odontogenic differentiation and mineralization in stem cells from human exfoliated deciduous teeth (SHEDs). Mineralization in the bones and teeth is in part controlled by pericellular levels of inorganic phosphate (Pi), a component of hydroxyapatite, and inorganic pyrophosphate (PPi), an inhibitor of mineralization. The progressive ankylosis protein (gene ANKH; protein ANKH) and ectonucleotide pyrophosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 72 publications
3
24
0
Order By: Relevance
“…We also observed that either TNF treatment or enforced TNF expression further enhanced the mineral deposition in TNAP-overexpressing bNPs in vitro. Our gene expression analysis showed that TNF decreased ANKH mRNA by approximately 50%, in agreement with reports showing that TNF promotes ectopic mineralization in hASMCs by suppressing ANKH mRNA expression by half 21 , and other authors in several tissues showing induced matrix mineralization and 50% reduction of ANKH mRNA expression in target cells as a result of TGF-β1 57 , ePi/forskolin 58 , or IL-1β 24 , 25 treatment, whereas basic fibroblast growth factor (bFGF) 59 and IL-6 60 treatment increased ANKH mRNA by twofold while still driving mineralization. Regarding ENPP1 expression modification by cytokines, it has been reported that IL-1β decreases ENPP in hMSCs 23 and in bNPs 25 , mRNA for ENPP was also reduced in rat ASMCs by ePi/forskolin treatment 58 , and ENPP is decreased in IDD patients with advanced degeneration and mineralization 56 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed that either TNF treatment or enforced TNF expression further enhanced the mineral deposition in TNAP-overexpressing bNPs in vitro. Our gene expression analysis showed that TNF decreased ANKH mRNA by approximately 50%, in agreement with reports showing that TNF promotes ectopic mineralization in hASMCs by suppressing ANKH mRNA expression by half 21 , and other authors in several tissues showing induced matrix mineralization and 50% reduction of ANKH mRNA expression in target cells as a result of TGF-β1 57 , ePi/forskolin 58 , or IL-1β 24 , 25 treatment, whereas basic fibroblast growth factor (bFGF) 59 and IL-6 60 treatment increased ANKH mRNA by twofold while still driving mineralization. Regarding ENPP1 expression modification by cytokines, it has been reported that IL-1β decreases ENPP in hMSCs 23 and in bNPs 25 , mRNA for ENPP was also reduced in rat ASMCs by ePi/forskolin treatment 58 , and ENPP is decreased in IDD patients with advanced degeneration and mineralization 56 .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding ENPP1 expression modification by cytokines, it has been reported that IL-1β decreases ENPP in hMSCs 23 and in bNPs 25 , mRNA for ENPP was also reduced in rat ASMCs by ePi/forskolin treatment 58 , and ENPP is decreased in IDD patients with advanced degeneration and mineralization 56 . Treatment of human deciduous teeth stem cells with IL-6 had little effect on ENPP1 mRNA expression, whereas bFGF resulted in nearly a doubling of baseline levels 59 , 60 , and rat endplate chondrocytes increase ENPP mRNA following TGF-β1 treatment 61 . There appears to be a complicated tissue- and factor-specific influence on ANKH and ENPP expression modulation.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple levels of cell-autonomous and extrinsic signals tightly control fate determination of MSCs [ 11 , 16 – 19 ]. It is possible that extrinsic factors derived from the local niche and systemic environment shape the epigenetic landscape of stem cells, which influences the gene expressions of stemness markers to dictate cell fate [ 20 26 ]. Previous studies revealed that designing artificial niches through adding extracellular matrix (ECM) proteins or growth factors in the ex vivo culture condition proved to be an effective way to maintain the potential capability of BMSCs [ 7 , 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the timing of evaluation, because SOX9 gene expression was assessed at 28 days after bFGF stimulation, which may be too late to detect SOX9 upregulation by bFGF. On the other hand, bFGF controlled the maintenance of stemness in MSCs [ 29 , 30 ], and suppressed the cellular senescence of MSCs by downregulating transforming growth factor β2 (TGF-β2) [ 31 ]. Cellular senescence downregulates the therapeutic potential of human MSCs by reducing their migratory, homing, and immunoregulatory abilities in vivo [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%